1980
DOI: 10.1007/bf00020075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kinetin on the photosynthetic apparatus of Sinapis alba

Abstract: The influence of kinetin during the development of primary leaves of Sinapis alba was investigated. Kinetin treatment (6 ppm) induced an increase of dry weight, of soluble reducing sugars, soluble protein, chlorophylls, carotenoids and cytochrome f; a higher ratio of chlorophyll a to chlorophyll b, higher rates of CO2 fixation per fresh weight and higher activity of nitrite reductase, were also found. These effects are comparable with strong and blue light adaptations. On the other hand, the Hill activity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The development of plastids at high light intensities to sun-type chloroplasts, and at low quanta fluence rates to shade-type chloroplasts, has been summarized earlier [37,39,45]. The formation of sun-type like chloroplasts can be simulated with low intensity blue light [14,42,63], and by the application of cytokinins [15,37,65] or the fungicide triadimefon [38]. Shade-type like chloroplasts, in turn, are formed in low intensity red light [14,37,63] and under the influence of the photosynthetic herbicides bentazon [41,46], diuron [41,52] and metabenzthlazuron [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The development of plastids at high light intensities to sun-type chloroplasts, and at low quanta fluence rates to shade-type chloroplasts, has been summarized earlier [37,39,45]. The formation of sun-type like chloroplasts can be simulated with low intensity blue light [14,42,63], and by the application of cytokinins [15,37,65] or the fungicide triadimefon [38]. Shade-type like chloroplasts, in turn, are formed in low intensity red light [14,37,63] and under the influence of the photosynthetic herbicides bentazon [41,46], diuron [41,52] and metabenzthlazuron [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Fedtke [7] supposed that the reduction of sugar content may be responsible for the low-light adaptation reaction. In a previous paper [26] we demonstrated that the initial and most powerful effect of kinetin was the drastic rise in the content of soluble reducing sugars. Therefore it can be supposed that variations in the sugar content play an important role in adaptation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Growth conditions of plants of Sinapis alba were as described earlier [26]. Beginning with day 20 after sowing, IAA in a concentration of 4ppm (22.8/~M; aqueous solution; pH 4.8) was sprayed on the upper surface of the primary leaves daily.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations